Städtebau-Ausstellungen in Deutschland 1910-2010. - Petz, Ursula von (TH Zürich, NSL, 2008)
Anlässlich der 100-jährigen Wiederkehr der ersten Städtebau-Ausstellung in Deutschland lässt der Beitrag einerseits die damalige Ausstellung in Teilen wiedererstehen und andererseits die Entwicklung der Disziplin Städtebau Revue passieren und beleuchtet so schließlich auch den aktuellen Stand der derzeitigen Planungswissenschaften. Der Städtebau konstituiert sich als eigenständige Disziplin mit einem im Jahre 1909 und einer Bauausstellung im darauf folgenden Jahr in Berlin. Die Autorin gibt einen Überblick über die Geschichte dieser und der weiteren Städtebau-Ausstellungen in Deutschland und die darin integriert, über die Theorien, die sie begründen, sowie Ziele, die sie verfolgen: Stuttgart - Weißenhofsiedlung 1927, Berlin - Deutsche Bauausstellung 1931, Köln - die Werkbund-Ausstellung "Die Neue Zeit" 1932, Hannover - Constructa 1951, Berlin Interbau 1957, IBA Berlin 1979-1987, IBA Emscher Park 1989-1999.

The paper focuses on the history of a 100-year tradition of organizing town planning exhibitions in Germany: In Berlin in 1910, as part of a competition to design new housing estates, it was decided to exhibit the contributions and results to the public. The two events could be seen as crucial for the development of modern town planning for their content as well as procedure (or theory and practice). With sharp criticism against the 19th century city, Berlin and elsewhere, which consisted mostly of the "famous" rented blocks on a grid road system with hardly any open space inbetween, the alternative concepts presented in the exhibition for more modest, lower housing estates surrounded by green and open spaces has to be seen as a new approach to urban life. Besides, new forms of green and open space, not just as trees planted along a road or some modest playground or little park, but as an urban network, were claimed as a basic need for better urban living conditions that would reinforce youth, and offer citizens and young people the chance to live and grow up in "light, sun and air". The article describes how the tradition of presenting town planning ideas to the public in special exhibitions, as well as discussing it in professional terms, which started nearly a century ago in 1910 in Berlin, has not only survived but continued to develop till today.
City planning exhibitions in Germany 1910-2010.
Keywords: Baugeschichte; Institutionengeschichte; Bauausstellung; Stadtplanung; Städtebau; Planungstheorie; Planungspraxis; Leitbild